2014
DOI: 10.1186/2045-9912-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction following desflurane versus sevoflurane general anesthesia in elderly patients: a randomized controlled trial

Abstract: As life expectancy increases, more patients ≥65 years undergo general anesthesia. Anesthetic agents may contribute to postoperative cognitive dysfunction, and incidence may differ with anesthetic agents or intraoperative anesthesia depth. Responses to anesthetic adjuvants vary among elderly patients. Processed electroencephalography guidance of anesthetic may better ensure equivalent cerebral suppression. This study investigates postoperative cognitive dysfunction differences in elderly patients given desflura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 40 publications
(53 reference statements)
2
28
0
6
Order By: Relevance
“…The analysis included only five studies, while three additional related articles were excluded due to inappropriate outcome reporting. 15,17,25 There was significant heterogeneity in the meta-analysis of several recovery events, most likely related to differences in study protocols. In addition, due to the limited number of included studies, it was not possible to perform a funnel plot to test publication bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis included only five studies, while three additional related articles were excluded due to inappropriate outcome reporting. 15,17,25 There was significant heterogeneity in the meta-analysis of several recovery events, most likely related to differences in study protocols. In addition, due to the limited number of included studies, it was not possible to perform a funnel plot to test publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…2 Because of age-related degeneration in respiratory and cardiovascular function and other associated systemic diseases, elderly patients are at risk of experiencing anaesthesia complications. Postoperative cognitive dysfunction (POCD) was found to be present in 25.8% of elderly patients at 1 week after surgery, and 9.9% of elderly patients at 3 months after surgery. 3 In addition, elderly patients who developed POCD were twice as likely to develop dementia in the following 3-7 years after anaesthesia and surgery compared with those unaffected by POCD.…”
Section: Introductionmentioning
confidence: 99%
“…an impairment of memory, concentration and intellectual abilities, is a well-known complication after both cardiac and non-cardiac operations [1][2][3][4][5][6] . Various studies have observed that the incidence of this condition ranges from 10% to 65% postoperatively 7,8 and is influenced by factors such as type of surgery 1,[9][10][11][12][13] , the age of patients 14,15 , and the timing of postoperative cognitive examination 1,[15][16][17][18][19][20][21][22][23][24][25][26][27] . Despite extensive investigation [27][28][29][30][31] , firm conclusions that link risk factors to the development and duration of this condition remain elusive.…”
mentioning
confidence: 99%
“…[45] Besides awareness prevention, use of anesthesia depth monitoring helps avoid anesthetic overdosing, thereby achieving earlier recovery and preventing PONV. [4] Greater intraoperative depth of anesthesia was observed to lead to better postoperative analgesia[67] but could not be confirmed by a study, in which both BIS and ETC of desflurane were measured.…”
Section: Discussionmentioning
confidence: 99%